2015
DOI: 10.1007/s10854-015-3230-x
|View full text |Cite
|
Sign up to set email alerts
|

Tin whisker growth on electroplated Sn multilayers

Abstract: As one of the key reliability issues, tin whisker problem has perturbed the electronics industry for several decades. Developing an effective way to mitigate the growth of tin whiskers is of great importance. In this study, we develop a novel multilayer method through alternately plating bright Sn and matte Sn layers to control the tin whisker growth. The samples of bilayer, trilayer and quadlayer were fabricated and stored at 55°C/85 % relative humidity and room temperature to evaluate the whisker growth. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…18 If the reduction proceeds to lower cathodic potentials, the π electron system is restored and the concentration of oxygen functional groups decays monotonically, while the electrocatalytic properties (probed using ferro/ferri-cyanide system) are improved. 18 Similar conclusions were derived by Liu et al 25 who also demonstrated a reduced charge transfer resistance with the decrease of the GO reduction potential using impedance measurements. However, despite an intensive research, there is still no consensus regarding the impact of different structural and chemical parameters on the capacitive performance of graphene-based materials.…”
Section: Introductionsupporting
confidence: 67%
“…18 If the reduction proceeds to lower cathodic potentials, the π electron system is restored and the concentration of oxygen functional groups decays monotonically, while the electrocatalytic properties (probed using ferro/ferri-cyanide system) are improved. 18 Similar conclusions were derived by Liu et al 25 who also demonstrated a reduced charge transfer resistance with the decrease of the GO reduction potential using impedance measurements. However, despite an intensive research, there is still no consensus regarding the impact of different structural and chemical parameters on the capacitive performance of graphene-based materials.…”
Section: Introductionsupporting
confidence: 67%
“…[159] This prominent enhancement of photocatalytic performance and efficient separation of photoinduced electron-hole pairs are attributed to the construction of a Z-scheme structure and reliable interfacial interaction of BiVO 4 /g-C 3 N 4 . A series of techniques, [115] nÀBi 12 O 17 Cl 2 / pÀBiOI photocatalytic oxidation of 2,4-DCP, RhB, phenol, BPA, and tetracycline hydrochloride [119] nÀSr 2 TiO 4 / pÀBi 5 O 7 I photocatalytic oxidation of MO [120] pÀBiOI/ nÀBiPO 4 photocatalytic oxidation of MO and phenol [121] pÀBiOBr/ nÀLa 2 Ti 2 O 7 photocatalytic oxidation of RhB and phenol [122] pÀBiOI/ nÀBi 2 O 2 CO 3 photocatalytic oxidation of RhB [123] pÀBiOI/ nÀgÀC 3 N 4 photocatalytic oxidation of BPA [124] nÀBiPO 4 / pÀBiOBr Photocatalytic activity for formaldehyde Oxidation; photocatalytic oxidation of RhB [125126] pÀBiOCl/ nÀBiVO 4 photocatalytic oxidation of RhB [127] pÀBiOI/ nÀBiOIO 3 photocatalytic oxidation of MB [30] pÀCuBi 2 O 4 / nÀBiWO 6 photocatalytic oxidation of MB and photocatalytic reduction of Cr 2 O 7 2À [128] pÀBiOCl/ nÀBiVO 4 photocatalytic oxidation of MO [129] pÀBi 2 O 3 / nÀBi 2 WO 6-x F 2x photocatalytic oxidation of RhB [130] pÀBiOCl/ nÀBi 2 O 2 CO 3 photocatalytic oxidation of RhB [131] pÀBi 2 O 3 / nÀBi 2 WO 6 photocatalytic oxidation of RhB and phenol [114] pÀBiOI/ nÀMnNb 2 O 6 degradation of antibiotics (TC, oxytetracycline, ciprofloxacin and doxycycline) [132] pÀBiOBr/ nÀCeO 2 photocatalytic oxidation of RhB, MB and phenol [133] pÀBiOBr/ nÀBi(C 2 O 4 ) OH photocatalytic oxidation of RhB [134] pÀBi 2 O 3 / nÀBi 2 MoO 6 photocatalytic oxidation of RhB and 2,4-DNP [135] pÀBiOBr/ nÀZnO photocatalytic oxidation of phenol [136] pÀBiOBr/ nÀBiOIO 3 photocatalytic oxidation of RhB, MB, MO and crystal violet [137] pÀBiOBr/ nÀTiO 2 photocatalytic oxidation of RhB and photocatalytic H 2 generation [138] pÀBiOI/ nÀBrÀBi 2 O 2 CO 3 photocatalytic oxidation of MO [139] pÀBiOI/ nÀBi 2 Sn 2 O 7 photocatalytic oxidation of RhB [140] pÀBiOI/ nÀSnS 2 photocatalytic oxidation of RhB [141] nÀFe 2 O 3 / pÀBiOI photocatalytic oxidation of RhB…”
Section: Z-scheme Heterojunctionsmentioning
confidence: 99%
“…The need for lead-free electronics manufacturing has rekindled interest in the problem of tin (Sn) whiskers. Sn whisker grows spontaneously from an electrodeposited tin coating on a copper substrate at room temperature, which can lead to well-documented system failures in electronics [1][2][3][4]. Although this phenomenon was first identified and reported in the late 1940s there is still a lot of uncertainty about the detailed mechanisms of Sn whisker growth.…”
Section: Introductionmentioning
confidence: 99%